Toxicology service phone-in assistance, 2006-2009 (2011)
Objective Establishing phone-in assistance's epidemiological profile as part of Colsubsidio's toxicology service (a Colombian healthcare-providing institution -IPS) from 2006-2009. Methods This was a population-based descriptive study of 594 toxicology service telephone consultations; it also concerned doctors attending patients seeking advice due to exposure to toxic substances. Results In terms of exposure to and consumption of toxic substances regarding age group, patients aged 1 day to 6 years reached a peak, males being most affected by accidental causes. Patients aged 13 to 18 also reached a peak, females being most affected due to attempting suicide by deliberately poisoning themselves. The findings revealed that accidental poisoning was the major cause, followed by suicide attempts. There was no significant difference between percentages. Medicaments appeared to be the main substance causing poisoning amongst the study population. Therapeutic treatment was predominantly used. Other variables taken into account in the study included poisoning distribution as time elapsed and poisoning route. Conclusions The poisoning profile identified in this investigation was comparable (to a large extent) to what has been reported in the specialized literature on the rest of the American continent. It should be stressed that there was no significant statistical difference between accidental poisonings and suicide-related poisoning. This study constitutes a statistical reference for Bogota and similar cities.